Effectiveness of typodont, quail egg and virtual simulation for ultrasonic periodontal scaling teaching among pre-clinical students: a randomized trial - Jiarun Fu; Zhentao Lao; Li Gao; Shiwen Wu; Xin Huang; Chuanjiang Zhao; Panpan Wang (BMC, 2024)
Abstract Background This study aimed to compare the efficacy of three different techniques, namely virtual simulation technology (VS), traditional pathological typodont (TT), and quail egg (QE), in pre-clinical training of periodontal ultrasonic scaling. It also aimed to propose an integrated teaching approach for ultrasonic scaling teaching. Methods This single-blind randomized multi-arm trial enrolled 108 fourth-year students from Guanghua School of Stomatology at Sun Yat-sen University. The participants were randomly, evenly assigned to VS, TT, or QE group. First, the participants received theoretical review on ultrasonic scaling and demonstrative teaching. Then in the 90-minute operation training by group, students used traditional typodont equipped in head-simulators, raw quail eggs, or scaling module of the UniDental VS system respectively. Then all participants practiced on pathological models for 30 min. In the final operation examination, participants were instructed to remove the supra- and sub-gingival calculi pre-set on designated teeth by ultrasonic scalers within 30 min. Their performances were evaluated by residual calculus rate and a multi-perspective scoring scale. After the examination, questionnaires were provided to assess the teaching effects of each method and the fidelity of VS. Statistical analysis was carried out using one-way, two-way ANOVA, and multiple t-test. Results Students in VS group had significant higher total test scores than QE group (87.89 ± 6.81, 83.53 ± 8.14) and TT group (85.03 ± 6.81). VS group scored higher in several dimensional comparisons with the other two groups, especially in difficult situations. QE group had higher scores particularly in force application and supra-gingival scaling. TT group scored the highest in pivot stability practice and body position training. Students gave higher scores when assessing the fidelity of VS than experienced teachers. Conclusion The study highlights the importance of specialized pre-clinical training on ultrasonic scaling for dental students. The methods adopted in current study (VS, TT and QE) each offered unique advantages in education, which can be combined to create an integrative teaching procedure. This procedure aims to provide an effective, advisable and normative pre-clinical training procedure for ultrasonic scaling. By utilizing the strengths of each method, dental educators can deliver high-quality training and ensure that students are well-prepared for clinical practice.